Prognostic Value of Hepatitis B Virus Infection in Very Young Patients With Curatively Resected Breast Cancer: Analyses From an Endemic Area in China - Li, Ning; Zhong, Qing-Qi; Yang, Xian-Rong; Wang, Qi-Cai; Zhang, Di-Tian; Zheng, Shaoquan; Yang, Lu; Wei, Wei-Dong (Frontiers in Oncology, 2020)
Background: Hepatitis B virus (HBV) infection has been associated with the risk and prognosis of many malignancies. Nevertheless, the association between HBV and the prognosis of breast cancer is unclear. The objectives of this study were to investigate the prognostic role of hepatitis B surface antigen (HBsAg) and to integrate HBsAg to establish nomograms for better prognostic prediction of very young patients with breast cancer. Methods: This analysis was performed retrospectively in a cohort of 1012 consecutive very young (≤35 at diagnosis) patients who received curative resection for breast cancer. The significance of HBsAg in the prognosis of these patients was investigated. Univariate and multivariate analyses were used to identify independent variables for disease-free survival (DFS) and overall survival (OS). Nomograms were built based on those identified variables. Results: Overall, 140 of the 1012 patients (13.8%) were seropositive for HBsAg. The median follow-up was 67.9 (95% CI, 64.4-71.4) months for the entire population. The HBsAg-positive cohort had significantly inferior DFS (HR, 1.66; 95% CI, 1.07-2.56; P=0.021) and OS (HR, 1.75; 95% CI, 1.10-2.79; P=0.016) as compared with the HBsAg-negative cohort. The rates of 10-year DFS and OS were 77.4% and 73.0% in the HBsAg-positive group and 84.1% and 85.6% in the HBsAg-negative group, respectively. In multivariable analysis, HBsAg status was identified as an independent significant unfavorable prognostic factor for DFS (P=0.01) and OS (P=0.04) in very young patients with breast cancer. Nomograms were established and displayed good calibration and acceptable discrimination. The C-index values for DFS and OS were 0.656 (95% CI: 0.620–0.691) and 0.738 (95% CI: 0.697–0.779), respectively. Based on the total prognostic scores (TPS) of the nomograms, 3 different prognosis groups were identified for DFS and OS. Conclusions: HBsAg is an independent unfavorable prognostic factor for DFS and OS in very young patients with curatively resected breast cancer, and nomograms integrating HBsAg provide individual survival prediction to benefit prognosis evaluation and individualized therapy.